Current status on obesity in childhood and adolescence: Prevalence, etiology, co-morbidities and management - BEREKET, ABDULLAH (Elsevier Ltd, 2016)
Obesity and its associated co-morbidities increased throughout the world in the last 50 years, mainly due to increased amount of consumption of calorie-dense food and sedentary lifestyle. It is essential to combat with obesity at all available means and levels, including medical, societal and international measures. Childhood obesity persists into adulthood depending on the presence of parental obesity and severity of obesity. There are several windows of opportunity for interventions starting from pre-conception, to in-utero nutritional environment, from early infancy to adolescence to prevent obesity. In this paper, epidemiology, etiopathogenesis, co-morbidities, prevention and treatment of obesity in children will be reviewed. © 2016 Elsevier Ltd.
Keywords: Adolescence; Childhood; Metabolic syndrome; Obesity; Overweight; Pediatric